Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue. Issue 3 (28th November 2022) - Zhang, Wenfeng; Deng, Hengwei; Fu, Yuting; Fu, Weixuan; Weng, Shaoping; He, Jianguo; Dong, Chuanfu
Abstract: Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.